24=-11y-8+3y

Simple and best practice solution for 24=-11y-8+3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24=-11y-8+3y equation:


Simplifying
24 = -11y + -8 + 3y

Reorder the terms:
24 = -8 + -11y + 3y

Combine like terms: -11y + 3y = -8y
24 = -8 + -8y

Solving
24 = -8 + -8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '8y' to each side of the equation.
24 + 8y = -8 + -8y + 8y

Combine like terms: -8y + 8y = 0
24 + 8y = -8 + 0
24 + 8y = -8

Add '-24' to each side of the equation.
24 + -24 + 8y = -8 + -24

Combine like terms: 24 + -24 = 0
0 + 8y = -8 + -24
8y = -8 + -24

Combine like terms: -8 + -24 = -32
8y = -32

Divide each side by '8'.
y = -4

Simplifying
y = -4

See similar equations:

| 60*0.2= | | 3w-4=-16 | | -32=w/5-7 | | -v+131=180 | | 31=-u+184 | | 205=96-y | | -25=4u+3 | | 82-(4-6)2= | | 25n^8-49n^7-2n^6=0 | | -3+w=-4 | | -6=u-4 | | 5(2x-9)+3x=4x-18 | | 13=0.5((4x-10)+(3x+8)) | | 9x-(x+4)=2x+32 | | (1/7(x))+((1/7)x+1)+29=x | | 2x^1/2-7x^1/4+3=0 | | 63=.5h*9 | | 4x+7=54 | | 1/2*(3/5((2^3)-6))+1/5 | | 7/5x^2-7/9x-4/3x | | 1/2*3/5((2^3)-6)+1/5 | | 82x+4x=68.5 | | 5y+1/9=6y+5/9 | | 0.50x+0.05(80)=0.25(64) | | -8(x+5)+3=-37 | | 5x/14-3x/14-11x/14= | | -3x+2y+z=4 | | (3x+2)(5x-1)= | | (x-74)/x=0.4 | | m^4+4m^2+1=0 | | 0.08-0.01(x+2)=-0.02(3-x) | | 99=.5h+11 |

Equations solver categories